Role of Corpus Gastritis and cagA-Positive Helicobacter pylori Infection in Reflux Esophagitis - Queiroz, Dulciene Maria Magalhães (American Society for Microbiology, 2002)
Considering that the role of Helicobacter pylori infection in gastroesophageal reflux and reflux esophagitis (GERD) is still controversial and that the role of virulence markers of the bacterium has not been evaluated in most studies of GERD, we investigated the association among H. pylori infection with cagA-positive and -negative strains, corpus gastritis, and GERD in a large group of patients by controlling for confounding factors. We studied prospectively 281 consecutive adult patients: 93 with GERD and 188 controls. H. pylori infection status was diagnosed by culture, by the preformed urease test, with a carbolfuchsin-stained smear, and by histology. The cagA status was determined by PCR of H. pylori isolates and gastric biopsy specimens. H. pylori infection was diagnosed in 191 (68.0%) of 281 patients. Among the 93 patients with GERD, 84 presented with mild or moderate esophagitis and 9 presented with severe esophagitis. In the multivariate analysis, the age of the patients and the degree of oxyntic gastritis were associated with GERD. Among the strains isolated from patients with GERD and from the control group, 24.4 and 66.9%, respectively, were positive for cagA (P < 0.001). Compared to infection with cagA-negative strains, infection with cagA-positive H. pylori strains was associated with a more intense gastritis in the corpus (P = 0.001). cagA status (odds ratio [OR] = 0.16, 95% confidence interval [CI] = 0.07 to 0.40), gastritis of the corpus (OR = 0.69, 95% CI = 0.48 to 0.99), and age (OR = 1.04, 95% CI = 1.01 to 1.07) were associated with GERD. In conclusion, the study provides evidence supporting the independent protective roles of cagA-positive H. pylori strains and the degree of corpus gastritis against GERD.